Letter (copy) : Mr. James Wheeler - Citrine, Walter, 1887-1983
034-0176-001 WMC/WJG/AC/92 International 21st October, 1937. Mr. F. Herrington, South Islington Labour Party, 295 Upper Street, N. 1. Dear Mr. Herrington, Mr. JAMES WHEELER. In reply to your letter of 20th October, we would suggest that the person to whom you refer should approach the Secretary of the Spanish Embassy, 24 Belgrave Square, W.1. and ask him if he can give her information about the death of her son. Should there be no satisfactory result we will ourselves make enquiries of our colleagues in France, in order to see whether they can indicate someone who might be able to give the details required. Yours faithfully, General Secretary. 292/946/34/176